2011
DOI: 10.1186/1748-7161-6-24
|View full text |Cite
|
Sign up to set email alerts
|

Is decreased bone mineral density associated with development of scoliosis? A bipedal osteopenic rat model

Abstract: BackgroundAn association between adolescent idiopathic scoliosis and osteopenia has been proposed to exist. It is still not clear whether there is such an association and if so, whether osteopenia is a causative factor or a consequence. Our previous pilot studies have suggested the presence of osteopenia in scoliotic animals. The aim of this study was to investigate the development of scoliosis in an unpinealectomized bipedal osteopenic rat model, implementing osteoporosis as a causative factor.MethodsFifty Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Idiopathic scoliosis is the most common spinal deformity in human, affecting more than 2% of the adolescent population and resulting in more than 600, 000 physician visits annually [ 1 ]. Recent studies have discovered several risk factors associated with progression to a severe curve, including the delayed age of first menstruation [ 2 ], lower bone age [ 3 ], high Cobb’s angle at presentation [ 4 ], and decreased bone density [ 5 ]. In addition, some scholars report that there is a consistent loss of kyphosis in thoracic scoliosis patients compared with normal control or patients with thoracolumbar curves [ 6 , 7 ] and scoliosis progresses faster in patients with minor thoracic kyphosis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Idiopathic scoliosis is the most common spinal deformity in human, affecting more than 2% of the adolescent population and resulting in more than 600, 000 physician visits annually [ 1 ]. Recent studies have discovered several risk factors associated with progression to a severe curve, including the delayed age of first menstruation [ 2 ], lower bone age [ 3 ], high Cobb’s angle at presentation [ 4 ], and decreased bone density [ 5 ]. In addition, some scholars report that there is a consistent loss of kyphosis in thoracic scoliosis patients compared with normal control or patients with thoracolumbar curves [ 6 , 7 ] and scoliosis progresses faster in patients with minor thoracic kyphosis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although it was first assumed that this finding may be the consequence of a problem in the vitamin D synthesis or metabolism, no defects in this system or suggestive genetic polymorphisms could be identified [33,34]. In a study to clarify the role of osteopenia in scoliosis, Dede et al [35] demonstrated that there was no difference in rates of Fig. 4 Results of histomorphometric analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we selected 5-week-old rats for the operation. At 5 weeks of age, all rats were rendered bipedal by amputating the forelimbs at a high humeral level and the tails at the root under anesthesia, as previously described 18 , 19 . After removing the forelimbs and tail, the bipedal rats were housed in special high cages with raised food and water to ensure that they maintained a standing posture most of the time; both food and water were gradually elevated in the cage as the bipedal rats grew.…”
Section: Methodsmentioning
confidence: 99%
“…Because the quadrupedal rodent spine is unlike the human spine and is not subjected to the same postural and dynamic mechanical forces required for the development of scoliosis 17 , bipedal rat and mouse models have been used to study the mechanism of AIS 18 , 19 . Therefore, in this study, an adolescent bipedal rat model was chosen to study the roles of estrogen in the onset and development of AIS.…”
Section: Introductionmentioning
confidence: 99%